Enhancing Educational Practices and Overcoming Systemic Challenges in Developing Inclusive Education for Students with Special Needs - Hasriadi, Hasriadi; Hidayat, Rahmat Nur; Tazlim, Andi Nur (Educia Journal, 2024)
The purpose of this research is to identify how different educational arrangements have been changed and developed with regards to the needs of special learners; the instructional methods being used, issues hindering the implementation of effective strategies, and systems that ensure inclusive practice. Evaluating the population in question, the qualitative research precisely collected data for the chosen topic via interviews with educators, administrators and parents pointing to special education population. Studies show that IEP goals and objectives, use of technology and modified instructional approaches are essential to help increase student’s learning capabilities. However, this study also reveals some of the definitive barriers, such as the lack of resources, inadequate preparation of teachers and prejudices prevailing in societies preventing the successful incorporation of IE for children. The participants called for the expansion of funds to meet the identified need for appropriate instructional materials, technology, and personnel. Furthermore, participants emphasized the need for the access to professional development which is all-embracing and on-going for teachers was pinpointed as another factor in enhancing of the quality of learning for the students with learning needs. Que interesantemente, an investigación también revela que las políticas deben ser mejor definidas y la comunidad y los padres deben estar más comprometidos para promover una educación inclusiva. Thus, the present research responds to the deficiency of the present knowledge base regarding the nature and potential approaches to mitigating systemic barriers in special education by comparing its results with the findings reported by other authors. The findings help us to make a better understanding of the concept of inclusive education and create a basis for further investigations designed to enhance learning achievements of children with learning disabilities.